Pengembangan Buku Penuntun Praktikum Biologi Tentang Materi Difusi Dan Osmosis Untuk Peserta Didik Kelas XI SMA - Yesi Putri Utami; Ristiono Ristiono (STKIP ROKANIA, 2022)
Biology learning is learning that is not just memorizing, but is learning that requires a high understanding and also requires practicum to strengthen theory. So we need a practical guide that can help students carry out practicum independently and improve students' science process skills. One of these guidelines is in the form of a Biology practicum manual which is specifically designed for practical activities. This study aims to develop a Biology Practicum Guidebook on Diffusion and Osmosis Materials for Class XI High School Students that is valid and practical. The development of this Biology practicum guide uses three stages of 4-D models, namely define, design, and develop. The object of this research is the Biology Practicum Guidebook on Diffusion and Osmosis Materials for Class XI High School Students. This Biology practicum guide was validated by 2 Biology Department lecturers, FMIPA UNP and 1 Biology teacher at SMAN 1 Luhak Nan Duo, then a practicality test was carried out by 1 Biology teacher and 30 students in Class XI MIPA SMAN 1 Luhak Nan Duo. The validation results of the developed Biology Practicum Guidebook show an average value of 87.51 with a very valid category. The results of the practicality test of the Biology Practicum Guidebook showed an average score of 92.67 from Biology teachers in the very practical category and 82.53 from students in the very practical category